Transcutaneous Electrical Nerve Stimulation to Reduce Pain With Medication Abortion: A Randomized Controlled Trial. Issue 1 (January 2021) - Goldman, Ariella R.; Porsch, Lauren; Hintermeister, Abigail; Dragoman, Monica
Abstract : OBJECTIVE: To evaluate whether high-frequency transcutaneous electrical nerve stimulation (hfTENS) reduces pain during medication abortion. METHODS: We conducted a randomized, placebo-controlled trial. Participants who were undergoing medication abortion with mifepristone and misoprostol through 70 days of gestation either received active 80 Hz hfTENS or sham to use for a minimum of 60 minutes within 8 hours of misoprostol. Maximum pain on an 11-point numerical rating scale at 8 hours after misoprostol was the primary outcome. We estimated 20 per group for 80% power to detect a 2-point difference and up to 10% attrition. Secondary outcomes included a maximum pain score at 24 hours, additional analgesia use, the difference in score before and after treatment, the experience of side effects, abortion outcomes, and acceptability. We collected data at baseline, time of misoprostol (0-hour), 8-hour and 24 hours using real-time electronic surveys, and at follow-up. RESULTS: Between June 2019 and March 2020, we screened 251 patients and randomized 40—20 each to hfTENS or sham—with one postrandomization exclusion and two patients lost to follow-up. Baseline characteristics were similar. Median maximum pain scores at 8 hours were 7.0 (interquartile range 3.0) and 10.0 (interquartile range 3.0) for hfTENS and sham, respectively. The distribution of these scores was lower among hfTENS users compared with sham (mean rank 15.17 vs 22.63, P =.036). High-frequency TENS users also experienced a significant reduction in posttreatment pain score (−2.0 [interquartile range 2.5] vs 0 [interquartile range 1.5], P =.008). We found no statistically significant differences in use of additional analgesia, distribution of maximum pain scores at 24 hours, side effects, or measures of acceptability. CONCLUSION: High-frequency TENS reduced maximum pain scores within 8 hours of misoprostol and reduced pain scores immediately after treatment compared with placebo. High-frequency TENS offers an effective nonpharmacologic option for pain management during medication abortion. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03925129. Abstract : High-frequency transcutaneous electrical nerve stimulation decreases pain during medication abortion with mifepristone and misoprostol.